ERP SYSTEM BUILDING, AND INTEGRATION WITH INTERNAL MAILING SYSTEM(IMS) - KHALED ABDULAZIZ (IJCONSIST JOURNALS, 2022)
The Enterprise Resource Planning systems have a role in the sustainable development of the organization, the principle of Enterprise Resource Planning systems is useful to improve the performance of the organization. This aper will focus on building Enterprise Resource Planning systems integrated with Internal Mailing System for ALTAMYZ ALRAEDAH company in Saudi Arabia to escalate the work performance and decision making. Afterwards, the researcher conducted a simple interview to the top manager to see the effectiveness of the system. (ERP) solutions are used to manage an organization's activities (accounting, procurement, compliance, production, project management and other distribution chain operations). Implementing Enterprise Resource Planning systems can have a variety of effects depending on the organization. The main purpose of the system being built is to alter the manual company data storage into ERP system integrated with IMS system. The research method used is a Qualitative research based on the interviews with top managers and employees. The result showed that the top managers of the company agreed that ERP system improves their working performance, while the IMS enables a better means of communication for a faster decision making.